Understanding the underestimation of self-report weight: The roles of narcissism and accountability. - Menna Price; Laura Douglas; Erica G Hepper; Laura L Wilkinson (PLoS ONE)
Self-reported height and weight is widely used to calculate Body Mass Index (BMI) and yet little is known about factors that affect accuracy. This study investigated the motivational characteristics-narcissism and social desirability-that influence the accuracy of self-reported weight and how they interact with accountability (telling participants that their weight will be verified). A two-way between-subjects design was used (accountable vs not accountable) with motivational moderators (narcissism and social desirability). Participants (N = 80; Mean Age = 34.63; 58.8% Female) were randomly allocated to accountable (told that their weight would be verified in a follow-up lab session) or not-accountable (no information given) conditions. In Session 1, participants self-reported motivational (social desirability and narcissism) and anthropometric (height and weight) measures online. In Session 2 (24 hours later), objective measures of height and weight were taken in the lab. There was a significant interaction between condition and maladaptive narcissism level. Being told that weight would be later verified improved accuracy of self-reported weight, but only for those low in maladaptive narcissism. Accountability improves the accuracy of self-report weight data, but not for individuals high in narcissism. Though based on a modest sample, these findings suggest that the under-estimation of self- report weight serves a self-protective function and maladaptive narcissism may be a useful covariate to include in research using self-report weight estimates.